Расчет нестационарного теплового режима помещения с теплоинерционными ограждающими конструкциями - Сулейменов, Уланбатор Сейтказиевич; Маляренко, В. А.; Костиков, А. О.; Камбаров, М. А.; Орлова, Н. А.; Загнойко, В. В. (НТУ "ХПИ", 2016)
У роботі подано нестаціонарну математичну модель і методику розрахунку теплового режиму приміщення з урахуванням теплоінерційних властивостей огороджувальних конструкцій в умовах теплообміну, як з навколишнім середовищем, так і сусідніми приміщеннями. Проведено тестові розрахунки модельного приміщення для різних режимів опалення.

A non-stationary mathematical model and methodology of calculation of the heat regime of room taking into account heat-inertial properties of structures fencing construction under the conditions of heat exchange both with an environment and by nearby rooms are presented in the paper. The test calculations of model room are carried out for the different modes of heating.
Calculation of non-stationary heat regime of room with the heat-inertial structures fencing construction
Keywords: теплоаккумулирующая способность; энергопотребление; ограждающие конструкции; уравнение теплопередачи; температурное поле; математическая модель